Comparative epidemiological study of breast cancer in humans and canine mammary tumors: insights from Portugal - Carvalho, Paulo Tiago; Niza-Ribeiro, João; Amorim, Irina; Queiroga, Felisbina; Severo, Milton; Ribeiro, Ana Isabel; Pinello, Katia (Frontiers in Veterinary Science, 2023)
Dogs spontaneously develop mammary gland tumors (MGT) and exhibit striking similarities in clinical and epidemiological characteristics to human breast cancer (HBC). Descriptive and comparative analysis of HBC and canine MGT with a focus on evaluating similarities and geographical distribution were the aims of this study. HBC cases were obtained from North Regional Oncological Registry (RORENO) (2010)(2011)(2012)(2013)(2014)(2015) and canine MGT cases from Vet-OncoNet (2019-2022). Analyses were performed based on published and well accepted classification systems (ICD-O-3.2 for humans and Vet-ICD-O-canine-1). Agestandardized incidence risks (ASIR) of Porto district municipalities were calculated using 2021 Portuguese census (INE) and data from the Portuguese animal registration system (SIAC).Among 7,674 HBC cases and 1,140 MGT cases, a similar age and sex distribution pattern was observed. Approximately 69.2% of HBC cases were between 40 and 69 years old, while 66.9% of MGT cases were diagnosed between 7 and 12 years old (mean age of 9.6 years, SD=2.6). In women, Invasive breast carcinoma Infiltrating Duct Carcinoma (8500/3) was the most common histological type (n=5,679, 74%) while in dogs it was the Complex Carcinoma (8983.1/3) (n=205, 39%). Cocker and Yorkshire Terriers exhibited the highest relative risks (3.2 and 1.6, p<0.05, respectively) when compared to cross breed dogs. The municipalities' ASIR of the two species exhibited a high correlation (R=0.85, p<0.01) and the spatial cluster analysis revealed similar geographic hotspots. Also, higher ASIR values both in women and dogs were more frequently found in urbanized areas compared to rural areas. This research sheds light on the shared features and geographical correlation between HBC and canine MGT, highlighting the potential of cross-species environmental oncology studies.